Beyond Crime Control: Can Peace Education Transform Criminology and Security Studies? An Appraisal from Iconic Open University, Sokoto - Mudassir Nasir; Uko Uko (Journal of Current Research and Studies, 2026)
This paper examines whether peace education, integrated into criminology and security studies curricula, can shift the emphasis of policing and security scholarship from reactive crime control toward preventive, community-centered, and restorative approaches. Using a qualitative conceptual–analytical methodology, the study synthesizes secondary data from scholarly literature, policy documents, and institutional curricular materials. It maps curriculum strengths and gaps, reflects on international exemplars of university–police partnerships, and analyses how open and distance learning (ODL) modalities—exemplified by the Iconic Open University, Sokoto (IOUS) can advance continuing professional development for serving officers. Findings indicate that peace education offers strong theoretical and pedagogical leverage to reorient criminology toward ethical reasoning, community engagement, and conflict transformation, but its impact is mediated by curriculum design, experiential learning opportunities, institutional partnerships, and infrastructural capacity. The paper concludes with policy recommendations for curriculum redesign, university–police collaboration, and ODL enhancement to ensure that peace education contributes meaningfully to police professionalization and security sector reform in Nigeria.